Association of Calpain (CAPN) 10 (UCSNP-43, rs3792267) gene polymorphism with elevated serum androgens in young women with the most severe phenotype of polycystic ovary syndrome (PCOS) - Anastasia, Karela; Koika, Vasiliki; Roupas, Nikolaos D.; Armeni, Anastasia; Marioli, Dimitra; Panidis, Dimitrios; George, Adonakis; Georgopoulos, Neoklis A. (Gynecological endocrinology, 2015)
Objectives: To highlight a possible association of Calpain (CAPN 10) gene UCSNP-43 polymorphism with hormonal and metabolic traits of young women with different phenotypes of polycystic ovary syndrome (PCOS). Design: PCOS women were genotyped for the CAPN 10 gene UCSNP-43 polymorphism. A comparison of clinical and biochemical features of women with PCOS stratified on the basis of the CAPN 10 gene UCSNP-43 variants was assessed. Methods: Anthropometric, hormonal and biochemical measurements were carried out in 668 PCOS women and 200 healthy controls. Subjects were also genotyped for the CAPN 10 gene UCSNP-43 polymorphism. The genotype frequency distributions between groups and controls were compared using the chi-square test. The association of the polymorphism with the clinical and biochemical features of the study cohort was estimated as well. Results: No association of the frequency of CAPN 10 gene UCSNP-43 polymorphism with PCOS was detected. No association of the polymorphism with the anthropometric, biochemical and hormonal features was detected both in PCOS and control women. The polymorphism was associated with serum Δ4 androstenedione (p = 0.018), as well as with 17-OH progesterone (17-hydroxyprogesterone) among women with PCOS phenotype A (p = 0.012). Conclusions: CAPN 10 gene polymorphism UCSNP-43 is deprived of a metabolic contribution to cardiovascular disease (CVD). However, due to its association with androgen excess in phenotype A, CAPN 10 gene polymorphism UCSNP-43 could be used as a genetic marker for CVD in young PCOS women. 目的：探究不同分型的多囊卵巢综合症（PCOS）年轻女性患者中，钙蛋白酶（CAPN 10）基因UCSNP-43的多态性与她们激素和代谢特征间可能的关系。 实验设计：检测PCOS女性CAPN 10基因UCSNP-43的多态性。依据CAPN 10基因UCSNP-43的变异型对PCOS患者进行分层，比较评估不同分层间的临床和生化特性。 方法：对668名PCOS女性和200名健康对照组女性进行人体测量学指标、激素和生化指标的检测。受试者均检测其CAPN 10基因UCSNP-43的基因型。实验组和对照组间基因型频率分布的比较采用卡方检验。同时对基因多态性与该队列研究中临床和生化特征间的相关性也进行了评估。 结果：未发现CAPN 10基因UCSNP-43多态性频率与PCOS有相关性。PCOS组和对照组均未检测到基因多态性与人体测量学指标、生化和激素指标有相关性。该基因多态性在表型A的PCOS女性中与血清Δ4雄烯二酮和17-OH孕酮（17-羟孕酮）相关（分别为p=0.018和p=0.012） 结论：CAPN 10多态基因UCSNP-43来源于其在心血管疾病（CVD）发展进程中对代谢方面的影响。但是，由于其与表型A中雄激素过多相关，CAPN 10多态基因UCSNP-43可作为年轻PCOS女性发生CVD的基因标记物。